2017
DOI: 10.1186/s13568-017-0514-y
|View full text |Cite
|
Sign up to set email alerts
|

The plant pathogen Gluconobacter cerinus strain CDF1 is beneficial to the fruit fly Bactrocera dorsalis

Abstract: Plant pathogens can build relationships with insect hosts to complete their life cycles, and they often modify the behavior and development of hosts to improve their own fitness. In order to unravel whether some bacteria that can make fruit rot could have developed symbiotic interactions with Bactrocera dorsalis, we studied the symbiont bacteria profiles of the fly. We identified the bacterium Gluconobacter cerinus strain CDF1 from the ovaries and eggs of the oriental fruit fly B. dorsalis and the amount of Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Gluconobacter is supposed to be the causative agent of the pineapple pink disease (Swings and De Ley, ). Recent studies confirmed the plant‐pathogenicity of Gluconobacter cerinus CDF1 (He et al ., ), which fastens the rottening of bananas while being beneficial for the development of its transmitting fruit fly Bactrocera dorsalis . Any specific involvements of T1‐LS from Gluconobacter in plant pathogenicity or animal interactions, however, still need to be demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Gluconobacter is supposed to be the causative agent of the pineapple pink disease (Swings and De Ley, ). Recent studies confirmed the plant‐pathogenicity of Gluconobacter cerinus CDF1 (He et al ., ), which fastens the rottening of bananas while being beneficial for the development of its transmitting fruit fly Bactrocera dorsalis . Any specific involvements of T1‐LS from Gluconobacter in plant pathogenicity or animal interactions, however, still need to be demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that some plants can release more β-caryophyllene after infection by some bacteria 2527 , and egg-surface bacteria can cause the fruit to rot 28 . Thus, we hypothesized that egg-surface bacteria are involved in increasing β-caryophyllene in fruits.…”
Section: Resultsmentioning
confidence: 99%
“…From this point of view, the increased volatile terpenoids or β-caryophyllene in bacteria-infested plants may be a defence response of plants and may contribute to inhibiting bacterial infection. Thus, it is not surprising that the increased β-caryophyllene in B. dorsalis host fruits was induced by egg-surface bacteria and demonstrated a role in host fruit defence against egg-surface bacteria since surface bacteria can cause fruit rot 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This species is significantly more abundant in OFM than PFM and may contribute to the different ratios of ABC transporters and the Two-component system. Gluconobacter cerinus was another species present in PFM and OFM, which may have a beneficial role as in the case of fruit flies where it can affect reproduction (46). Pantoea is a highly diverse genus that can cause plant diseases and human diseases but also have functions in habitat restoration and pesticide degradation (47).…”
Section: Discussionmentioning
confidence: 99%